A decision model for energy companies that sorts projects, classifies the project manager and recommends the final match between project and project manager - Oliveira,Elaine Cristina Batista de (2016)
Abstract This study presents an integrated model to support the process of classifying projects and selecting project managers for these projects in accordance with their characteristics and skills using a multiple criteria decision aid (MCDA) approach. Such criteria are often conflicting. The model also supports the process of allocating project managers to projects by evaluating the characteristics/types of projects. The framework consists of a set of structured techniques and methods that are deemed very appropriate within the context of project management. A practical application of the proposed model was performed in a Brazilian electric energy company, which has a portfolio of projects that are specifically related to the company´s defined strategic plan. As a result, it was possible to classify the projects and project managers into definable categories, thus enabling more effective management as different projects require different levels of skills and abilities.